2019
DOI: 10.1590/1678-4324-2019180039
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Thymoquinone on Sperm Parameters and Testosterone Level of Nicotine-Treated Sprague Dawley Rats

Abstract: Thymoquinone (TQ), the main constituent of the volatile oil derived from Nigella sativa has shown pharmacological benefits against various diseases while nicotine is an active component in cigarette that is known to be detrimental. This study was conducted to assess the ameliorating effects of TQ on sperm count, membrane, mitochondria and testosterone of nicotine-treated rats. Rats were randomized into four groups: control, nicotine, TQ, and nicotine with TQ. Nicotine (5 mg/kg bwt/day) was subcutaneously injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Both 7.5 and 15 mg/kg TQ had no effect on seminiferous tubules, tunica albuginea and germinal epithelium thickness and testis weight. Rosli et al (2019) demonstrated that oral administration of 5 mg/kg TQ to rats for 30 days significantly decreased the viable sperms, while the number of sperm and level of testosterone hormone was not affected by TQ, 35 which was similar to our results at level of 15 mg/kg TQ. It seems that the beneficial or detrimental effects of TQ on male reproductive system depend on the dose applied, and also the duration of administration.…”
Section: Discussionsupporting
confidence: 92%
“…Both 7.5 and 15 mg/kg TQ had no effect on seminiferous tubules, tunica albuginea and germinal epithelium thickness and testis weight. Rosli et al (2019) demonstrated that oral administration of 5 mg/kg TQ to rats for 30 days significantly decreased the viable sperms, while the number of sperm and level of testosterone hormone was not affected by TQ, 35 which was similar to our results at level of 15 mg/kg TQ. It seems that the beneficial or detrimental effects of TQ on male reproductive system depend on the dose applied, and also the duration of administration.…”
Section: Discussionsupporting
confidence: 92%
“…Gökçe et al (2011) [156] established that TQ administration in mice lessened interstitial space dilatation and the deleterious manifestations in testis caused by methotrexate. TQ demonstrated ameliorative potential against the detrimental effects of nicotine towards sperm count, membrane, mitochondria and testosterone level [157]. TQ ameliorated testicular damage and improved sperm quality in varicocele-induced adolescent rats by reducing apoptosis, oxidative stress, and lipid peroxidation [158].…”
Section: Effects Of Tq On Male Infertilitymentioning
confidence: 94%
“…Nigella sativa oil and its active constituents have been reported by several authors to improve sperm parameters. 12,30,31 Mahdavi et al, 31 reported that the antioxidant properties of Thymoquinone may be responsible for the neutralized free radicals in semen and improved sperm parameters. a: significant decrease (P<0.05) when compared with the control group.…”
Section: Effects Of Thymoquinone On Sperm Parameters In Lead Acetate-...mentioning
confidence: 99%
“…This work is licensed under the Creative Commons Attribution 4.0 International License caused by testicular injury through oxidative stress. 12 However, the role of TQ against lead acetate-induced nephrotoxicity in male Wistar rats has not been fully elucidated. Therefore, the present study investigated the ameliorative role of TQ on male reproductive functions in lead acetate-induced reproductive toxicity in male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%